FINANCIAL PERFORMANCE AND COMPANY VALUE OF SHARIAH BANKING IN INDONESIA - Murni, Sri (Archives of Business Research, 2021)
This research aims to understand the influence of CAR, FDR, NPF, and ROA to the Company Value of Shariah Banking in Indonesia. The study is done at the Indonesian Stock Exchange and Shariah Banking in Indonesia. The research object on the company financial report shariah banks in the form of financial reports the period of 2014 – 2019 is loaded in the Indonesian Capital Markets Directory as well as data originating from IDX, ICMD, and annual report. To test the hypotheses of variable X and variable Y simultaneously using the F, while based on partial use t. The data used was secondary data. In this research used time series data and cross section (pooling data), and based on the criteria, the number of sample which satisfies the criteria of as many as 8 shariah banks of 12 shariah banking as the population. The result showed that simultaneously CAR, FDR, NPF and ROA have significant impact on the company value. In partial CAR and ROA on this fact have a positive and significant on the company value, NPF have a negative and significant on the company value, and FDR have an insignificant for the company value. The result is expected to be a valuable input especially for investors as consideration in decision making of investing; also for the company management is expected to be a consideration in this matter, in addition, the result of this research can be an important reference to the similar research for the benefit of applied and science development